Saline is as effective as nitrogen scavengers for treatment of hyperammonemia. Issue 1 (December 2017) - Straten, G.; Velden, M.; Geijlswijk, I.; Favier, R.; Mesu, S.; Holwerda-Loof, N.; Ham, M.; Fieten, H.; Rothuizen, J.; Spee, B.; Verhoeven-Duif, N.
Abstract Urea cycle enzyme deficiency (UCED) patients with hyperammonemia are treated with sodium benzoate (SB) and sodium phenylacetate (SPA) to induce alternative pathways of nitrogen excretion. The suggested guidelines supporting their use in the management of hyperammonemia are primarily based on non-analytic studies such as case reports and case series. Canine congenital portosystemic shunting (CPSS) is a naturally occurring model for hyperammonemia. Here, we performed cross-over, randomized, placebo-controlled studies in healthy dogs to assess safety and pharmacokinetics of SB and SPA (phase I). As follow-up safety and efficacy of SB was evaluated in CPSS-dogs with hyperammonemia (phase II). Pharmacokinetics of SB and SPA were comparable to those reported in humans. Treatment with SB and SPA was safe and both nitrogen scavengers were converted into their respective metabolites hippuric acid and phenylacetylglutamine or phenylacetylglycine, with a preference for phenylacetylglycine. In CPSS-dogs, treatment with SB resulted in the same effect on plasma ammonia as the control treatment (i.e. saline infusion) suggesting that the decrease is a result of volume expansion and/or forced diuresis rather than increased production of nitrogenous waste. Consequentially, treatment of hyperammonemia justifies additional/placebo-controlled trials in human medicine.